Risk stratification of atherosclerotic cardiovascular disease in Chinese adults. Issue 2 (June 2016) - Yang, Xue-Li; Chen, Ji-Chun; Li, Jian-Xin; Cao, Jie; Lu, Xiang-Feng; Liu, Fang-Chao; Hu, Dong-Sheng; Liu, Xiao-Qing; Shen, Chong; Yu, Ling; Lu, Fang-Hong; Wu, Xian-Ping; et al.
Abstract: Objective: This study aims to determine the distribution of observed atherosclerotic cardiovascular disease (ASCVD) incidence in contemporary cohorts in China, and to identify cut-off points for ASCVD risk classification based on traditional criteria and new equations developed by Prediction for ASCVD Risk in China (China-PAR). Methods: The study populations included cohorts in the China-PAR project, with 34, 757 participants eligible for the current analysis. Traditional risk stratification was assessed by using Chinese guidelines on prevention of CVD and hypertension, and 5 risk groups were classified based on these guidelines after slight modification for available risk factors. Kaplan–Meier analysis was conducted to obtain the cumulative incidence of observed ASCVD events for all subjects and sub-groups. The predicted 10-year ASCVD risk was obtained using the China-PAR equations. Results: A total of 1922 ASCVD events were identified during an average follow-up of 14.1 years. According to the group classification based on traditional risk stratification, the observed 10-year risks for ASCVD were 4.61% (95% confidence interval [ CI ]: 4.11–5.10%) in the moderate-risk group and 8.74% (95% CI : 7.82–9.66%) in the high-risk group. Based on the China-PAR equations for risk assessment of ASCVD, those with predicted risks of <5%, 5–10%, and ≥10% could be classified into categories of low-, moderate-, and high-risk for ASCVD, respectively. Conclusion: The findings enable development of a simple method for classification of individuals into low-, moderate-, and high-risk groups, based on the China-PAR equations. The method will be useful for self-management and prevention of ASCVD in Chinese adults.